Training at Different Intensities as a Means of Preventing Overweight and Obesity in Children - Abderezzek, BOUDOUANI; Mohamed, OUDDAK; Taieb, GUERACHA; Salah, REBOUH; Tadjeddine, BENHIBA; Abdelkarim, RAHOU (Journal of Ecohumanism, 2025)
This study aims to determine the effectiveness of a training programme designed to reduce excess weight and prevent obesity in children. A training programme consisting of exercises of varying intensity, mainly based on high-intensity interval training (HIIT), to reduce excess weight and prevent obesity in children. The programme was intended for children under the age of 17 (boys and girls). We worked with a sample of 30 children (15 boys and 15 girls). The programme ran for 10 weeks, with an average of 4 sessions per week. It targeted body composition (fat mass and lean mass) and aerobic power. The research results confirm that HIIT (High-Intensity Interval Training) is very effective in combating obesity in young people because it burns a lot of fat, including visceral fat, improves cardio-metabolic fitness, increases muscle mass (which consumes more energy), and can even improve self-esteem, but it must be adapted to age and physical condition.